180 undergraduates from 13 public universities participate in the World Software Testing Program - Technology Education Leader, Sdn Bhd (2018)
The World Software Testing Program (WSTP) is a collaboration between Ministry of Higher Education, Universiti Malaysia Pahang (UMP), Technology Education Leader Sdn Bhd (TEL) and MicroFocus/HP. The program was carried out for 8 weeks between October through December 2017 and has successfully trained 180 Information Technology and Engineering undergraduates from 13 public universities. The program is under the Ministry of Higher Education’s Graduate Employability grant (GE).